Degradable PEGylated protein conjugates utilizing RAFT polymerization. (April 2015) - Decker, Caitlin G.; Maynard, Heather D.
Graphical abstract: Highlights: Degradable PEG-like, protein-reactive polymers were synthesized by RAFT polymerization. p(PEGMA- co -BMDO)-lysozyme conjugates were prepared with or without masked activity. Degradation of the polymers alone and from lysozyme was assessed. The activity of lysozyme reductively released from the polymer(s) was analyzed. Abstract: Poly(ethylene glycol) (PEG)–protein therapeutics exhibit enhanced pharmacokinetics, but have drawbacks including decreased protein activities and polymer accumulation in the body. Therefore a major aim for second-generation polymer therapeutics is to introduce degradability into the backbone. Herein we describe the synthesis of poly(poly(ethylene glycol methyl ether methacrylate)) (pPEGMA) degradable polymers with protein-reactive end-groups via reversible addition–fragmentation chain transfer (RAFT) polymerization, and the subsequent covalent attachment to lysozyme through a reducible disulfide linkage. RAFT copolymerization of cyclic ketene acetal (CKA) monomer 5, 6-benzo-2-methylene-1, 3-dioxepane (BMDO) with PEGMA yielded two polymers with number-average molecular weight ( Mn ) (GPC) of 10.9 and 20.9 kDa and molecular weight dispersities ( Đ ) of 1.34 and 1.71, respectively. Hydrolytic degradation of the polymers was analyzed by 1 H NMR and GPC under basic and acidic conditions. The reversible covalent attachment of these polymers to lysozyme, as well as the hydrolytic and reductive cleavage of the polymer from the protein, was analyzed by gel electrophoresis and mass spectrometry. Following reductive cleavage of the polymer, an increase in activity was observed for both conjugates, with the released protein having full activity. This represents a method to prepare PEGylated proteins, where the polymer is readily cleaved from the protein and the main chain of the polymer is degradable.